2016
DOI: 10.3390/ijms17111783
|View full text |Cite
|
Sign up to set email alerts
|

The Control of Calcium Metabolism in Zebrafish (Danio rerio)

Abstract: Zebrafish is an emerging model for the research of body fluid ionic homeostasis. In this review, we focus on current progress on the regulation of Ca2+ uptake in the context of Ca2+ sensing and hormonal regulation in zebrafish. Na+-K+-ATPase-rich cells (NaRCs), the specialized ionocytes in the embryonic skin and adult gills, play a dominant role in Ca2+ uptake in zebrafish. Transepithelial Ca2+ transport in NaRC, through apical epithelial Ca2+ channels (ECaC), basolateral plasma membrane Ca2+-ATPase (PMCA), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 116 publications
0
30
0
Order By: Relevance
“…Zebrafish are exposed to various Ca 2+ concentrations in their natural environment, from 0.01 mM (soft water) to 3 mM (hard water) ( Hoenderop et al, 2005 ; Pan et al, 2005 ; Lin and Hwang, 2016 ; USGS Office of Water Quality, 2017 ). Studies of fish have indicated strong CaSR expression in gills and the olfactory epithelium ( Loretz et al, 2004 ; Loretz, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish are exposed to various Ca 2+ concentrations in their natural environment, from 0.01 mM (soft water) to 3 mM (hard water) ( Hoenderop et al, 2005 ; Pan et al, 2005 ; Lin and Hwang, 2016 ; USGS Office of Water Quality, 2017 ). Studies of fish have indicated strong CaSR expression in gills and the olfactory epithelium ( Loretz et al, 2004 ; Loretz, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many hormones known to be critical to mammalian bone mineralization, including Vitamin D3, 304 parathyroid hormone, calcitonin were found to be important in zebrafish (Lin & Hwang, 2016). Using an optimized in situ hybridization protocol and qPCR analysis of FACS isolated 315 NaR cells, we found that Papp-aa is highly expressed in NaR cells.…”
Section: Nar Cells 243mentioning
confidence: 93%
“…The processes in the uptake and acid-base regulation in zebrafish have been comprehensively discussed in several previous reviews [ 1 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. However, no article has systematically reviewed the similarities and differences in the regulation of epithelial ion transporters between zebrafish and mammals during metabolic acidosis.…”
Section: Introductionmentioning
confidence: 99%